2019
DOI: 10.1039/c9ta03550h
|View full text |Cite
|
Sign up to set email alerts
|

Thin and robust organic solvent cation exchange membranes for ion separation

Abstract: An ultrathin and robust organic solvent cation exchange membrane (CEM) was successfully fabricated for the first time using dissolved Kevlar aramid nanofibers as the casting solution and 4-aminobenzenesulfonic acid (ABS) as the negatively charged functional group via an amide condensation reaction for ion separation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Generally, three typical characteristic regions, (1) the ohmic region, (2) the limiting current region, and (3) the over-limiting region, are displayed in the C-V curves. 50,51 The cross-linked membranes were tested and, as expected, showed better electrodialysis performance (CAPSF-100, CAPAF-80) compared with APSF and the commercial AEM (Neosepta AMX). As shown in Fig.…”
Section: Alkaline Stabilitymentioning
confidence: 55%
“…Generally, three typical characteristic regions, (1) the ohmic region, (2) the limiting current region, and (3) the over-limiting region, are displayed in the C-V curves. 50,51 The cross-linked membranes were tested and, as expected, showed better electrodialysis performance (CAPSF-100, CAPAF-80) compared with APSF and the commercial AEM (Neosepta AMX). As shown in Fig.…”
Section: Alkaline Stabilitymentioning
confidence: 55%
“…While most applications of ED occur in aqueous media, more attention is being given to organic media as well [264]. Zhao et al expanded the development of ED membranes to the treatment of waste organic streams [239,240,244,246]. Their ED membranes are based on poly (paraphenylene terephthalamide) nanofibers, which are characterized by their organic solvent resistance, high strength and outstanding thermal stability.…”
Section: Desalination Of Brackish Watermentioning
confidence: 99%
“…Commercial ion exchange membranes have been utilized for promotion of ion diffusion in membrane contactors . However, there is no long‐term stability evidence using ion exchange membranes for extraction purposes, although solvent resistance has been significantly improved . Song et al .…”
Section: Introductionmentioning
confidence: 99%
“…6,43,44 However, there is no long-term stability evidence using ion exchange membranes for extraction purposes, although solvent resistance has been significantly improved. 45,46 Song et al reported using sulfonated polyether ether ketone (SPEEK)/polyethersulfone (PES) blend membranes for lithium extraction 18 and separation of copper and nickel, 47 but with limited stability. Membranes made from ethylene vinyl alcohol (EVAL) have both hydrophobic solvent-resistant and hydrophilic ion permeable units, conferring solvent resistance.…”
Section: Introductionmentioning
confidence: 99%